2020
DOI: 10.2196/19016
|View full text |Cite
|
Sign up to set email alerts
|

Top Concerns of Tweeters During the COVID-19 Pandemic: Infoveillance Study

Abstract: Background The recent coronavirus disease (COVID-19) pandemic is taking a toll on the world’s health care infrastructure as well as the social, economic, and psychological well-being of humanity. Individuals, organizations, and governments are using social media to communicate with each other on a number of issues relating to the COVID-19 pandemic. Not much is known about the topics being shared on social media platforms relating to COVID-19. Analyzing such information can help policy makers and he… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

35
628
4
21

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 729 publications
(688 citation statements)
references
References 17 publications
35
628
4
21
Order By: Relevance
“…COVID-19-related content was identified on social media as follows: (a) updating new cases and their impact; (b) frontline reports on the epidemic and its prevention measures; (c) experts’ opinions on outbreaks of the infection; (d) frontline health services; and (e) global scope of the epidemic and identification of suspected cases [ 46 ]. The topics of greatest interest have also been identified: origin and transmission routes; magnitude of the impact on countries (infected and deaths, stress and fear, economy, movement restrictions), means of spreading, and risk control [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19-related content was identified on social media as follows: (a) updating new cases and their impact; (b) frontline reports on the epidemic and its prevention measures; (c) experts’ opinions on outbreaks of the infection; (d) frontline health services; and (e) global scope of the epidemic and identification of suspected cases [ 46 ]. The topics of greatest interest have also been identified: origin and transmission routes; magnitude of the impact on countries (infected and deaths, stress and fear, economy, movement restrictions), means of spreading, and risk control [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the mass media must take responsibility for providing correct information and facilitating comprehension by citizens, the role of the SFPT as a scholarly society was to contribute to the national effort to provide reliable drug information. In addition, monitoring social media helps to anticipate questions from the population and fake news [18]. Before the pandemic, actions to counter health‐related misinformation circulating in social media were well described.…”
Section: Discussionmentioning
confidence: 99%
“…This aspect was also explained by Cava and colleagues (2005) during the SARS outbreak, when many participants reported that inconsistent information from various sources led them to question the reliability of available information. Moreover, as shown by others (Dominguez-Salas et al, 2020), when adequate information is lacking, people double their efforts to ll the informative gap, sometimes choosing non-reliable sources such as social media and internet (Abd-Alrazaq et al, 2020;Cuan-Baltazar et al, 2020;Zhao et al, 2020) and contributing to creating overload. Therefore, during the COVID-19 lockdown, a condition in itself characterized by profound uncertainty, incomplete and inconsistent information, even if received by physician, together with an informative overload may have cast doubt on the reliability of information and on the trust placed in the health professionals, consequently generating higher levels of distress.…”
Section: Discussionmentioning
confidence: 98%